Investigação experimental do microfresamento da liga de titânio Ti-6Al-4V - Santos, Aline Gonçalves dos (2020)
Micro-Machining has gained greater visibility over time, due to the trends that industries are showing to produce small parts, being biomedicine one of the main areas that demand smaller components. In this context, micromilling of biomaterials is an important process. Therefore, the present work was developed with the main objective of experimentally investigating the micro-milling of the Ti-6Al-4V titanium alloy. For this, the machining temperature, the tool wear, the formation of burrs, the surface quality, the morphology of the chips and the influence of the feed per tooth on the quality of the microchannels were analyzed. In addition, the process simulation was performed using the AdvantEdgeTM program. For the performance of the experimental tests, a four-axis CNC micro-milling machine and a carbide-coated and uncoated carbide with nominal diameter of 400 µm were used. T-type thermocouples were welded to the workpiece surface for maximum temperature measurement during the process. To evaluate the wear by reducing the diameter of the micromill, images have been taken after each test using the Scanning Electron Microscope (SEM). Burrs were quantified using a methodology developed in the present work and roughness was measured by means of a profilometer. The results showed that the temperature increases from the up milling to the down side and that this variable becomes larger with tool wear. Adhesion and microchipping were the main forms of wear identified. The larger minor cutting edge angle was found to help reduce flank wear on the minor clearance surface. The burrs were larger on the down side of the channel. When employing the uncoated tool, the roughness tended to decrease with the machined length. With the coated tool, no change in roughness value was observed with tool wear. Continuous and spheroidals chips were identified. Also, it was defined a range of values for the advance that provides better roughness when analyzing the Ra, Rq, Rt, Rz, Rsk and Rku, under the analyzed conditions, being from 0.20 to 0.30 µm / tooth.